Derivatização dos esteroides fucosterol e campesterol e avaliação biológica dos seus derivados - Silva, Francisco Erivaldo Freitas da (2019)
The steroids fucosterol (F) and campesterol (C) were isolated from Lobophora variegata and Palythoa caribaeorum, respectively. The goal of this study was to evaluate the activities of the steroids F and C, and their derivatives F-1 to F-12, and C-1 to C-12, aiming to establish the structure-activity relationship. The present work describes the structural modifications of steroids F and C, as well as the antibacterial activity against the strains of Klebsiella pneumoniae (ATCC 10031), Escherichia coli (ATCC 10536), Pseudomonas aeruginosa (ATCC 15442), Streptococcus mutans (ATCC 0046) and Staphylococcus aureus (ATCC 6538), on Aedes aegypti larvae, as well as on the human cancer cell lines: MCF-7 human tumor cell lines (breast carcinoma), HL-60 (promyelocytic leukemia), and HCT-116 (colorectal cancer) of its derivatives. It is noteworthy that from the fucosterol twelve derivatives were obtained: (3β,20R,24E)-3-acetoxystigmasta-5,24(28)-diene (F-1), (3β,20R,24E)-3-butoxystigmasta-5,24(28)-diene (F-2), (3β,20R,24E)-3-hexanoxystigmasta-5,24(28)-diene (F-3), (3β,20R,24E)-3-benzoxystigmasta-5,24(28)-diene (F-4), (3β,20R,24E)-3-succinoxystigmasta-5,24(28)-diene (F-5), (3β,20R,24E)-3-hexadecanoxystigmasta-5,24(28)-diene (F-6), (3β,20R,24E)-(3)-4-fluorobenzoxystigmasta-5,24(28)-diene (F-7), (3β,20R,24E)-(3)-4-chlorobenzoxystigmasta-5,24(28)-diene (F-8), (3β,20R,24E)-(3)-4-bromobenzoxystigmasta-5,24(28)-diene (F-9), (3β,20R,24E)-(3)-4-nitrobenzoxystigmasta-5,24(28)-diene (F-10), (3β,20R,24E)-3-formyloxystigmasta-5,24 (28)-diene (F-11), and (3β,20R)-stigmastan-3-ol (F-12). This is the first report on the F-3, F-5, and F-7 to F-11 derivatives. Additionally, derivatives from the campesterol were also prepared: (3β,20R,24R)-3-acetoxyergost-5-ene (C-1), (3β,20R,24R)-3-butoxyergost-5-ene (C-2), (3β,20R,24R)-3-benzoxyergost-5-ene (C-4), (3β,20R,24R)-3-succinoxyergost-5-ene (C-5), (3β,20R,24R)-3-hexadecanoxyergost-5-ene (C-6), (3β,20R,24R)-(3)-4-fluorobenzoxyergost-5-ene (C-7), (3β,20R,24R)-(3)-4-chlorobenzoxyergost-5-ene (C-8), (3β,20R,24R)-(3)-4-bromobenzoxyergost-5-ene (C-9), (3β,20R,24R)-(3)-4-nitrobenzoxyergost-5-ene (C-10), (3β,20R,24R)-3-formyloxyergost-5-ene (C-11), and (3β,20R,24R)-ergostan-3-ol (C-12). Derivatives C-7, C-8, C-9 and C-11 are being reported for the first time. The derivatives were purified by silica gel chromatography and were obtained in good yields (68-98%). The structures of these substances were characterized by spectroscopic (IR, 1H NMR and 13C NMR) and spectrometric (MS) methods. Campesterol (C) and its semisynthetic derivatives C-1 to C-12 were submitted to bioassays on Aedes aegypti larvae, but did not show satisfactory results. The cytotoxic activity of the steroids F and C and its derivatives was investigated using the MTT method, however, no sample showed inhibition. The antibacterial activity of all derivatives was evaluated by means of the microdilution method and with the exception of the F-11 derivative, all the samples showed activity against Gram-positve (S. aureus e S. mutans) or Gram-negative bacteria (E. coli, P. aeruginosa e K. pneumoniae), or against the two cell strains (S. aureus, S. mutans, E. coli, P. aeruginosa e K. pneumoniae). It is noteworthy that the F-12, C-7 and C-9 derivatives presented moderate activity.